2021
DOI: 10.1215/00031283-8661833
|View full text |Cite
|
Sign up to set email alerts
|

InterestingFellowor Tough OldBird?

Abstract: English has many words to refer to an adult man, e.g. man, guy, dude, and these are undergoing change in Ontario dialects. This paper analyzes the distribution of these and related forms using data collected in Ontario, Canada. In total, N = 6788 tokens for 17 communities were extracted and analyzed with a comparative sociolinguistics methodology for social and geographic factors. The results demonstrate a substantive language change in progress with two striking patterns. First, male speakers in Ontario were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Based on the premise that lexical choices are influenced by similar conditioning factors that operate on grammatical and phonological variation, Tagliamonte and colleagues probed the sociolinguistic underpinnings of the system of third-person male adult noun referents in Ontario English (Franco & Tagliamonte, 2021; Tagliamonte, 2022). The authors found that guy was making traction over competing variants such as man , a change led predominantly by young men.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the premise that lexical choices are influenced by similar conditioning factors that operate on grammatical and phonological variation, Tagliamonte and colleagues probed the sociolinguistic underpinnings of the system of third-person male adult noun referents in Ontario English (Franco & Tagliamonte, 2021; Tagliamonte, 2022). The authors found that guy was making traction over competing variants such as man , a change led predominantly by young men.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the semantic field of third-person male adult noun referents is rife with variation, examining how this system has evolved holds promise for insights into the factors governing lexical variation and change in real time. Recent work on Ontario English shows that this lexical domain is in flux, with factors such as gender and age influencing speakers’ choices (Franco & Tagliamonte, 2021; Tagliamonte, 2022). Against the backdrop of this work, the present study examines the system of third-person male adult noun referents in earlier stages of the English language, specifically in Old and Middle English.…”
mentioning
confidence: 99%
See 1 more Smart Citation